Clinical practice recommendations on kidney management in methylmalonic acidemia: an expert consensus statement from ERKNet and MetabERN - Servais, Aude; Zacchia, Miriam; Dehoux, Laurène; Shroff, Rukshana; Brassier, Anais; Taurisano, Roberta; Kölker, Stefan; Oh, Jun; Ariceta, Gema; Stojanovic, Jelena; Hörster, Friederike; Strologo, Dello; et al. (Kidney international. Reports, 2024)
Methylmalonic acidemias (MMAs) are rare inherited metabolic diseases with multiorgan involvement. Chronic kidney disease (CKD) is a common complication, leading to kidney failure, dialysis, and kidney transplantation (KT). The objective of these guidelines was to develop clinical practice recommendations focusing on specific aspects of the kidney management of this disease. Development of these clinical practice recommendations is an initiative of the European Reference Network for Rare Kidney Diseases in collaboration with the European Reference Network for Hereditary Metabolic Disorders and included pediatric and adult nephrologists, metabolic specialists, as well as liver and kidney transplant specialists. CKD has become a significant clinical issue that requires specific follow-up in both pediatric and adult departments. Creatinine-based formulae significantly overestimate kidney function and the estimation of estimated glomerular filtration rate (eGFR) is more accurate using cystatin C. Besides usual kidney indications, acute dialysis may be required in emergency in case of acute metabolic decompensation to clear metabolic toxins. Long-term dialysis may be initiated for clearance of toxic metabolites. Long hours on hemodialysis (HD) and/or daily dialysis are required. The indications for transplantation in MMA are a high rate of metabolic decompensations, a high burden of disease and difficult metabolic control. Transplantation is also indicated in case of long-term complications. Combined liver-kidney transplantation (LKT) should be preferred in patients with MMA with CKD. Possible calcineurin inhibitors (CNIs) induced neurotoxicity was described in patients with MMA requiring immunosuppressive treatment monitoring and adaptation. Overall, 13 statements were produced to provide guidance on the management of CKD, dialysis, and transplantation in pediatric and adult patients with MMA.